STUDY ON NOISE POLLUTION DUE TO THE MINING ACTIVITIES FROM PESTEANA NORTH PERIMETER - Nicoleta-Maria MIHUȚ (Fiabilitate şi Durabilitate)
Knowledge noise exposure level is important because it has the effect of lowering of work ability, accuracy and efficiency of movement, and increased energy expenditure required to perform a given exercise. Also, noise is an important cause of frequency and increasing the number of work accidents by preventing perception of sound signals, decreasing and attention distractions, balance disorders, visual disturbances (mitigation of perception of colors and forms).